Corporate Governance Mechanism, Company Size Financial Performance and Sustainability Reporting - Ligar Hardika, Andhika; T. H. Manurung, Daniel; Mulyati, Yati (International Journal of Engineering and Technology, 2018)
The importance of sustainability reporting for companies to be able to know the role of the company in disclosing social responsibility and the implementation of corporate sustainability as a manifestation of corporate governance mechanisms, company size and financial performance. This study uses a stratified random sampling method for companies that have revealed sustainability reports and those that do not disclose sustainability reports. The research method uses logistic regression, with a sample of 13 non-financial companies listed on the Indonesia Stock Exchange. Based on the results obtained, it can be seen that the mechanism of corporate governance consisting of independent commissioner variables has a negative influence on sustainability reporting, institutional ownership variables have a positive influence on sustainability reporting, managerial ownership variables have a negative influence on sustainability reporting, audit committee variables have a negative effect on sustainability reporting, the variable size of the company gives a negative influence on sustainability reporting, and financial performance variables which are leverage variables have a negative influence on sustainability reporting.Â Â